Social media in the curriculum and co-curriculum: pre-service teachers and their collegiate peers - Heiberger, Greg A., author; Folkestad, James, advisor; Junco, Reynol, committee member; Aragon, Antonette, committee member; Coke, Pamela, committee member (Colorado State University. Libraries, 2013)
Although use of social media by students has been shown to be nearly ubiquitous, many K-12 school systems have banned its use on their campuses or use between their teachers and students. In contrast, many collegiate faculty have utilized social media in their teaching. Social media has been shown to assist faculty in engaging with students, helping students engage with content outside of class and sound implementation into the curriculum has been show to have positive educational impacts. Data from a sample of two thousand and fifty-six college students across two land-grant institutions is compared between pre-service teachers and their collegiate peers. Pre-service teachers reported using Twitter in the curriculum more, were more inspired by the use of social media use by their faculty, used social media more on their own for educational purposes and had a stronger belief that social media can be used for educationally relevant purposes than their collegiate peers.
Keywords: Facebook; higher education; K-12; pre-service; social media; Twitter